Effects of lactose-containing stevioside sweeteners on dental biofilm acidogenicity - Fernanda Cristina Mendes de Santana GIONGO; MUA Bruna; Clarissa Cavalcanti Fatturi PAROLO; Anette CARLÉN; Marisa MALTZ (Sociedade Brasileira de Pesquisa Odontológica, 2014)
The aim of this study was to evaluate the effect of a commercial lactose-containing stevioside sweetener on biofilm acidogenicity in vivo. Nine volunteers refrained from brushing their teeth for 3 days in five phases. On the 4th day of each phase, the pH of the biofilm was measured by the "Strip method". Interproximal plaque pH was measured before and up to 60 minutes after a 10 mL mouthrinse for 1 minute with the test solutions: I - sweetener with 93% lactose and 7% stevioside; II - sweetener with 6.8% saccharin, 13.6% cyclamate, and 0.82% stevioside; III - 18% sucrose solution (positive control); IV - mineral water (negative control); and V- 93% lactose solution. The results revealed that the most pronounced pH fall was found with sucrose (positive control), followed by the 93% lactose solution, the sweetener with lactose + stevioside, the sweetener with saccharin + cyclamate + stevioside, and finally water (negative control). According to the area under the curve, the two sweeteners containing stevioside were significantly different, and the sweetener with lactose + stevioside was significantly different from water but not from sucrose. The critical pH for dentin demineralization (pH ≤ 6.5) was reached by all volunteers after rinsing with sucrose solution, lactose solution, and the stevioside + lactose sweetener. Analysis of the data suggests that lactose-containing stevioside sweeteners may be cariogenic, especially to dentin.